1991
DOI: 10.1200/jco.1991.9.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of hypercalcemia and leukocytosis with cachexia in a human squamous cell carcinoma of the maxilla in athymic nude mice: a novel experimental model of three concomitant paraneoplastic syndromes.

Abstract: Hypercalcemia and leukocytosis may occur in conjunction as paraneoplastic syndromes associated with malignant disease. Here we describe a human squamous cell carcinoma of the maxilla that was associated with hypercalcemia and leukocytosis, and also cachexia. The primary tumor was surgically removed and established in permanent cell culture. When either primary tumors or cultured tumor cells were inoculated into nude mice, the nude mice developed the same paraneoplastic syndromes as those which occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Furthermore, herbimycin A inhibited the capacity of mature osteoclasts to form pits on dentine slices and suppressed bone resorption in organ cultures of fetal rat long bones. More importantly, we found that herbimycin A decreased and prevented rhIL-la-or tumor-induced hypercalcemia, both of which are associated with increased osteoclastic bone resorption in vivo (14,15 None of the currently available inhibitors of bone resorption are entirely satisfactory. Estrogens have only been used effectively in postmenopausal females and the mode of action ofestrogen remains unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, herbimycin A inhibited the capacity of mature osteoclasts to form pits on dentine slices and suppressed bone resorption in organ cultures of fetal rat long bones. More importantly, we found that herbimycin A decreased and prevented rhIL-la-or tumor-induced hypercalcemia, both of which are associated with increased osteoclastic bone resorption in vivo (14,15 None of the currently available inhibitors of bone resorption are entirely satisfactory. Estrogens have only been used effectively in postmenopausal females and the mode of action ofestrogen remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Ca2" was determined using a calcium pH analyzer (model 634; Corning, Medfield, MA) as described ( 15). Body weight of animals was measured (Lum-O-Gram; Ohaus Scale Corporation, Florham Park, NJ).…”
Section: Murine Marrow Cell Culture Systemmentioning
confidence: 99%
“…Cells (1 ϫ 10 5 ) were suspended in 0.1 ml of PBS and injected into the left heart ventricle of 4-wk-old, female BALB/c-nu/nu mice (Harlan Industries, Houston, TX) with 27-gauge needle under the anesthesia with pentobarbital (0.05 mg/gram). Animals were kept in our animal facilities for 4 to 7 wk as described (17). Weight of animals and excised tumors was determined by using a digitalized weigher (Lum-O-Gram ™ ; Ohaus Scale Corporation, Florham Park, NJ).…”
Section: Mda-231:a Human Breast Cancer Cell Linementioning
confidence: 99%
“…Purification of PPE-Initial steps of the purification were described earlier (2,3). Crude PPE was run through a DE-52 column (Whatman Labsales) (4.8 ϫ 60 cm, Kontes) equilibrated with 0.1 M Tris-HCl, pH 7.5.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have found that systemic administration of extracts of the porcine pancreas (PPE) 1 that have been prepared according to the methods described by Takaoka et al (1) reproducibly decrease blood ionized calcium (Ca 2ϩ ) concentrations in normal mice and inhibit bone resorption, which is stimulated by parathyroid hormone (PTH), interleukin-1␣, prostaglandin E 2 , tumor necrosis factor, transforming growth factor ␣, and 1,25-dihydroxyvitamin D 3 (1,25D 3 ) in organ cultures of fetal rat long bones (2). Inhibition of bone resorption by PPE was associated with inhibition of osteoclast formation (3).…”
mentioning
confidence: 99%